Analysis of cell cycle regulator proteins in non-small cell lung cancer. Issue 1 (23rd December 2003) - Esposito, V; Baldi, A; Tonini, G; Vincenzi, B; Santini, M; Ambrogi, V; Mineo, T C; Persichetti, P; Liuzzi, G; Montesarchio, V; Wolner, E; Baldi, F; et al.
Abstract : Background/Aims: Abnormalities of the proteins involved in cell cycle checkpoints are extremely common among almost all neoplasms. This study aimed to investigate the expression of four components of the cell cycle machinery—p21, p16, p53, and proliferating cell nuclear antigen (PCNA)—in non-small cell lung cancer (NSCLC). Methods: The expression of p21, p16, p53, and PCNA was examined in 68 well characterised NSCLC specimens using immunohistochemistry. The coregulation of these proteins and their influence on survival were analysed using both univariate and multivariate analyses. Results: By univariate analysis, the expression of all the proteins examined, except for PCNA, was significantly correlated with survival. In multivariate analysis, the only immunohistochemical parameter able to influence overall survival was p16, confirming the hypothesis that the RB–p16 tumour suppressor pathway is inactivated in most lung cancer samples. Finally, the group of patients with NSCLC who were negative for both p21 and p16 had a significantly shorter overall survival. Conclusions: These results suggest that loss of control of cell cycle checkpoints is a common occurrence in lung cancers, and support the idea that functional cooperation between different cell cycle inhibitor proteins constitutes another level of regulation in cell growth control and tumour suppression.